Pengelolaan Wakaf Dan Kehartabendaan Di PDM Surakarta - Hilmy Luayyin, Reza; , Dr. M. Abdul Fattah Santoso, M.Ag; , Dra. Mahasri Shobahiya, M.Ag (2015)
Waqf development in Indonesia is arguably not as advanced as in other countries that have known Islam first. That's because the new 2004 Indonesia's new legislation has endowments that really set about endowments and no longer oriented to the socio-economic field, but it is possible to be conducted into the economic field of production. In addition, the law also regulates the forms in which endowments not only in the form of land, but also intangible money or goods. In Surakarta today land has become scarce due to the development in each region in Surakarta is becoming increasingly rapid. Muhammadiyah Surakarta has a major role in the welfare of the people. Muhammadiyah Surakarta trying to help meet the needs of the community in various fields. To be able to continue to help the public welfare will be established Waqf Council is ready to help Persyarikatan Muhammadiyah in order to prosper the economic life of society takes many roles including through endowments. Here, the role of Waqf Council in the management is very important. The issues outlined in this paper is what factors are the basis for the establishment of endowments in Muhammadiyah Surakarta? And what is the most dominant factor in determining the endowments at Muhammadiyah Surakarta? The aim of this study are (1) To determine the development of Islamic legal theory related to waqf (2) To be able to know how should the management of waqf in order to maximize appropriate Islamic shari'ah. From these results, it is expected to be useful for people and the Muhammadiyah itself, especially regarding the management of waqf and as a scientific reference for further research. From these results we concluded that the management of waqf in Surakarta Muhammadiyah said to have a good and successful. This is evident from the management of waqf directed towards economic production. Factors which became the basis for setting endowment is, benefits and purpose. The most dominant factor is the factor of the benefits and purpose.